2008
DOI: 10.1111/j.1464-5491.2008.02604.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maternal ghrelin and leptin in healthy mothers and mothers with Type 1 diabetes

Abstract: In a population of pregnant women with expected changes in leptin levels as previously reported, ghrelin levels were lower in T1DM pregnancies at 20 and 30 weeks. This may have implications for fetal development and requires further study in diabetes, particularly in pregnancies that result in macrosomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In studies performed with type 1 diabetic pregnant women and lactating mothers with GDM, serum ghrelin concentrations were found to be lower than those of the control group (31,32). A limited amount of data is available on umbilical cord ghrelin concentrations.…”
Section: Discussionmentioning
confidence: 80%
“…In studies performed with type 1 diabetic pregnant women and lactating mothers with GDM, serum ghrelin concentrations were found to be lower than those of the control group (31,32). A limited amount of data is available on umbilical cord ghrelin concentrations.…”
Section: Discussionmentioning
confidence: 80%
“…Our results also suggest that ghrelin participates in the adaptation to the caloric imbalance of diabetic pregnancy and may play a similar role in pregnancy-related complications. Few reports have evaluated plasma ghrelin concentrations in women with diabetes and their offspring, although Kos et al (23) found lower plasma ghrelin levels at the end of pregnancy in women with T1DM. However, this finding was not replicated by Hehir et al (24), and Lappas et al (25) reported lower plasma ghrelin concentrations in women with GD, with persistence of this abnormality at 12 weeks post-partum predicting incident maternal diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that ghrelin levels did not differ between pre-term and at-term neonates (30). Nevertheless, maternal ghrelin at the end of a pregnancy is not correlated with fetal birth weight or placental weight (23), although there are no data regarding maternal serum ghrelin concentrations in pre-term neonates. These data suggest that maternal ghrelin may help control fetal growth, and ghrelin may be needed for fetal adaptation to abnormal uterine conditions, such as hyperglycemia (31).…”
Section: Discussionmentioning
confidence: 99%
“…93,94 In normal pregnancy, the peak leptin concentration is around 28 weeks 91 with little change from 20 to 30 weeks gestation. 95 However, in T1DM, there is a significant decline in free leptin levels from 20 to 30 weeks gestation. 95 It is therefore unlikely that leptin accounts for late changes in insulin requirements.…”
Section: Maternal Factors Affecting Insulin Requirements In Pregnancymentioning
confidence: 99%
“…95 However, in T1DM, there is a significant decline in free leptin levels from 20 to 30 weeks gestation. 95 It is therefore unlikely that leptin accounts for late changes in insulin requirements. The diabetogenic effect of IGF-1 is well documented.…”
Section: Maternal Factors Affecting Insulin Requirements In Pregnancymentioning
confidence: 99%